SWOT Analysis of Indian Agroforestry - Srinidhi, H.V.; Chauhan, Sanjeev K.; Sharma, S.C. (Indian Journal of Agroforestry, 2020)
During the last 25 years, agroforestry has been considered as a panacea for maladies of intensive agriculture. The increasing awareness on importance of trees for economic and environmental benefits is the strong driving force behind adoption of agroforestry. The principles of agroforestry rooted in ecological, economic and equity, offers sustainable land use system. But even today, agroforestry in India is thinly perceived and remains unexploited due to many predicaments from research to   operation. However, it has been dealt more on component rather than on system basis. This demands concerted effort to collate, evaluate, and disseminate basic knowledge gained through research and narrow down the gap between research and operation. The analysis of Strength, Weakness,  Opportunities and Threats (SWOT) of the technology offers constructive outlook on building strength, converting weakness into strength, encash opportunities and minimize threats. The insights gained on these features might lead to ideas for making them even better and extending the models, which are more sustainable and productive in other parts of the world. Strengths like basis of traditional knowledge, broad range of goods and services offered by the technology such as soil fertility  improvement, enhancement of biodiversity, carbon sequestration, dendroremediation, timber production, microclimate amelioration etc. are listed. Lack of understanding on interaction between the components (trees and crops), lack of information on biophysical and socio-economic environments in which the farmers operate, lack of focused research and development, generalization of recommendations, lack of proper marketing channel for agroforestry produce, failure to put adequate information in hands of policy makers and farmers, linkages and trade-offs between farm activities and environmental impacts, misconception of farmers with fragmented and marginal land holding are considered as weaknesses. Opportunities such as value added output (commercial crops-low volume high value crops), maximization of intangible benefits like carbon sequestration, dendroremedition through suitable design, involvement of private organization, enhancement of tree cover in the country etc. are highlighted. Threats include lack of orientation towards systematized research, biased economic support in the form of incentives and subsidies to select food crops, unorganized marketing for agroforestry produce, failure to develop human resources, inaccessibility to technology, etc. are some of the factors for consideration in promotion and adoption of agroforestry in the country. Exploitation of the untapped potential to increase the tree cover in the country through promotion of agroforestry is proposed as an engine to achieve the target of bringing 33 per cent of geographical area under tree cover. The social, political and administrative environment is in favour to bring trees back in farming system. Agroforestry has great future role for ensuring environmental sustainability and meeting sociological/economic objectives for achieving sustainable development goals in farming system. Only the agroforestry word is new but the practice is very old and after 25 years of its scientific background, the novelty lies in the realization that this land use system must attract systematic attention in approach worth exploring and developing in a more scientific way.